Quality-of-life index and its related factors during COVID-19 pandemic: A community-based study in Rashtian women/Iran - Asiyeh Namazi; Hassan Rafiey; Mirtaher Mousavi; Ameneh Setareh Forouzan; Gholamreza Ghaedamini Harouni (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: The changes in everyday life, caused by the COVID-19 pandemic, were rapid and unprecedented. This pandemic affected not only physical health but also well-being and life satisfaction. This study was designed to assess the status of a quality-of-life index and some related factors during the coronavirus pandemic in the public population of Rashtian women. MATERIALS AND METHODS: This cross-sectional study was performed on 784 Rashtian women who were selected by cluster random sampling between 2020 and 2021. The data collection tool was the Ferrans and Powers Quality of Life questionnaire, which has two parts: satisfaction and importance of life. Each section consists of four subscales: health and performance, social and economic, psychological/spiritual, and family. Data analysis was done using descriptive and analytic statistics. RESULTS: The mean score of the quality-of-life index in this study was 21.39 (of 30), which is higher than the mean level. The scores obtained from the satisfaction section were inferior to the similar questions in the important section. The findings showed that there was no statistically significant difference between the quality-of-life scores of women living in different urban areas (P > 0.05). CONCLUSION: The feeling of satisfaction increases the ability to cope with problems and mental pressures and improves the level of mental and physical health of couples and ultimately of all members of society. So although the overall quality of life was above average, appropriate interventions should be designed to maintain and improve their satisfaction.